The Influence of Music Therapy and Mindfulness Meditation in Reducing Anxiety in Elderly Individuals Undergoing Hemodialysis: A Systemic Review - Aminah Soemadi Al Djuwardi; Etty Rekawati; Dikha Ayu Kurnia (Indonesian Journal of Global Health Research, 2025)
Approximately 40-50% of hemodialysis patients are elderly who experience chronic health conditions such as end-stage renal disease. Routine medications, lifestyle changes, and side effects of treatment often cause anxiety. Anxiety is described as a disturbing feeling as a situation of fear or threat. The sensation of anxiety can consist of palpitations, tremors, nervousness, and shortness of breath, interfering with the procedure. hemodialysis. Long duration of treatment and physical discomfort caused by it cause anxiety. Therefore, appropriate and safe non-pharmacological therapy is needed in the elderly. Objective to reduce anxiety in the elderly undergoing hemodialysis. The search was conducted through journal sources from ScienceDirect, ProQuest, EBSCO, and Pubmed (2019-2024) with keywords using medical subject headings (MeSH) "older adults" OR "elderly" OR "geriatrics" AND "music therapy" AND "acoustic therapy" OR "mindfullness" OR "Meditation" from 2899 article, 3 articles reviewed consisting of 1 quasi-experimental article 2 RCT articles it was proven that music therapy has a positive effect and increases satisfaction during hemodialysis as well as mindful meditation has been shown to reduce anxiety. Music therapy as an intervention that is cheap, easy and safe for the elderly can reduce anxiety levels, as well as mindful meditation although more research is still needed to see the evidence base.